EVALUATION OF IN VITRO CULTURE MEDIA FOR THE MULTIPLICATION OF AVOCADO (PERSEA AMERICANA) ROOTSTOCKS CV. HASS, FREE OF PHYTOPHTHORA CINNAMOMI, IN THE DEPARTMENT OF TOLIMA - Olaya, Maria Angélica Beltrán; Gonzalez, Carlos Alberto Cervera; Fernández, Ana Milena Alonso (Seven Editora, 2025)
Avocado (Persea americana Mill) has become a crop of vital economic importance for Colombia; however, its productivity faces serious limitations due to the incidence of Phytophthora cinnamomi and the genetic variability resulting from seed propagation. The present study aimed to evaluate protocols for the in vitro establishment and multiplication of avocado rootstocks of the Criollo variety, ensuring pathogen-free plant material for the Department of Tolima. The methodology used nodal segments from mother plants previously analyzed by ELISA testing. Two disinfection protocols (P1 and P2) and three culture media (Murashige and Skoog – 50% MS, WPM, and Yasuda) were compared, evaluating contamination, oxidation, and viability variables. The results showed that Protocol 1 presented a significantly lower contamination rate (57.8%) compared with Protocol 2 (79.5%). Although oxidation was successfully controlled (7.31% overall) through the use of antioxidants and activated charcoal, microbial contamination remained the main challenge. It is concluded that the 50% MS medium combined with Protocol 1 provides the highest viability rate for the establishment stage, laying the groundwork for future phases of large-scale clonal multiplication.DOI: https://doi.org/10.56238/sevened2025.036-159